2018
DOI: 10.1002/adfm.201705537
|View full text |Cite
|
Sign up to set email alerts
|

New Strategy for Polysulfide Protection Based on Atomic Layer Deposition of TiO2 onto Ferroelectric‐Encapsulated Cathode: Toward Ultrastable Free‐Standing Room Temperature Sodium–Sulfur Batteries

Abstract: The room temperature (RT) sodium–sulfur batteries (Na–S) hold great promise for practical applications including energy storage and conversion due to high energy density, long lifespan, and low cost, as well based on the abundant reserves of both sodium metal and sulfur. Herein, freestanding (C/S/BaTiO3)@TiO2 (CSB@TiO2) electrode with only ≈3 wt% of BaTiO3 additive and ≈4 nm thickness of amorphous TiO2 atomic layer deposition protective layer is rational designed, and first used for RT Na–S batteries. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
126
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(128 citation statements)
references
References 58 publications
2
126
0
Order By: Relevance
“…An improved rational design of cathode materials to inhibit polysulfides dissolution is therefore urgently required for RT-Na/S batteries.Sh osts,w ith inherent polarization, are expected to enhance reactivity of Sa nd impede the shuttle effect. [9] These Sh ost cathodes with intrinsic sulfiphilic properties, such as metal sulfides [9] and metal oxides, [10] bind polysulfides and prevent their dissolution into the electrolyte.T hese however have been limited to TiO 2 , [11] Cu/CuS x , [12] Cu current foam, [13] and SSe [14] for construction of intrinsic sulfiphilic hosts in RT-Na/S batteries.M oreover,t he interaction between the polar surface of Sh osts with polysulfides is limited, and sodium polysulfides remain prone to dissolution into the electrolyte.R ecently,astrategy was established to circumvent this through reduction of polysulfides into shortchain sulfides,a nd production of Na 2 S. [15] This reduction conversion can obviate dissolution of sodium polysulfides and achieve,s imultaneously,a ni mproved capacity. [15] Tr ansitionmetal-based catalysts however have received significant attention because of low cost and abundance and, generally, excellent catalytic performance across ar ange of electrochemical reduction reactions.…”
mentioning
confidence: 99%
“…An improved rational design of cathode materials to inhibit polysulfides dissolution is therefore urgently required for RT-Na/S batteries.Sh osts,w ith inherent polarization, are expected to enhance reactivity of Sa nd impede the shuttle effect. [9] These Sh ost cathodes with intrinsic sulfiphilic properties, such as metal sulfides [9] and metal oxides, [10] bind polysulfides and prevent their dissolution into the electrolyte.T hese however have been limited to TiO 2 , [11] Cu/CuS x , [12] Cu current foam, [13] and SSe [14] for construction of intrinsic sulfiphilic hosts in RT-Na/S batteries.M oreover,t he interaction between the polar surface of Sh osts with polysulfides is limited, and sodium polysulfides remain prone to dissolution into the electrolyte.R ecently,astrategy was established to circumvent this through reduction of polysulfides into shortchain sulfides,a nd production of Na 2 S. [15] This reduction conversion can obviate dissolution of sodium polysulfides and achieve,s imultaneously,a ni mproved capacity. [15] Tr ansitionmetal-based catalysts however have received significant attention because of low cost and abundance and, generally, excellent catalytic performance across ar ange of electrochemical reduction reactions.…”
mentioning
confidence: 99%
“…[7] Additionally, the high-temperature operation results in safety, cost, and efficiency concerns. [9][10][11][12] To prevent the shuttle effect, several research studies have reported various attempts: (i) encapsulation with/infiltration into porous carbon, [13] (ii) coating of the cathode with conductive polymers, [14] (iii) formation of multiple metal oxides, [15] and (iv) development of a membrane to impede polysulfide diffusion to the anode. [9,10] However, RT-NaS still faces critical obstacles to practical use, such as the low electrical conductivity of sulfur, large volume expansion (≈170%), loss of active materials, etc.…”
mentioning
confidence: 99%
“…On the other hand, as shown in Figure d, Ma et al synthesized a complicated nanostructured S host with PAN‐derived porous C nanofibers as the matrix, embedded BaTiO 3 nanoparticles as a NaPS inhibitor, and an outer TiO 2 coating as an extra shield for the interior NaPSs. The “BaTiO 3 ‐C‐TiO 2 ” synergetic structure within the matrix thus effectively inhibited the shuttle effect and restrained the volumetric variation, leading to superior Na‐storage properties of their S cathode (CSB@TiO 2 ) . Wang's group created a composite by encapsulating S copolymer, poly(S‐pentaerythritol tetraacrylate) (PETEA), into a MOF‐5‐derived mesoporous carbon framework 16b.…”
Section: Chemical Interactionsmentioning
confidence: 99%
“…d) Schematic illustration of the preparation process for the CSB@TiO 2 electrode, and cycling performance comparison of C/S, C/S/BTO, and CSB@TiO 2 electrodes. Reproduced with permission . Copyright 2018, Wiley‐VCH.…”
Section: Chemical Interactionsmentioning
confidence: 99%